The Contemporary Discourse of Jihad in the Perspective of Jemaat Ahmadiyah Indonesia (JAI) - M. Gufron (Millati: Journal of Islamic Studies and Humanities, 2021)
Jihad is a term that represents the ambivalence of religion. It will continuously become a media of debate for some groups including Muslim and non-Muslim. According to JAI, jihad is striving in studying the teachings of Islam, then trying to practice them in daily life, and preaching in the way of Allah SWT. According to Ghulam Ahmad, there are three concepts of jihad, namely, small jihad, big jihad, and greatest jihad. Small jihad is now over because present condition is different from the past, they are no longer contextual.